A Bio‐Inspired and Biomass‐Derived Healable Photochromic Material Induced by Hierarchical Structural Design. Issue 1 (21st October 2019) - Wu, Bo; Lei, Yuan; Xiao, Yao; Wang, Yanjun; Yuan, Ye; Jiang, Liang; Zhang, Xi; Lei, Jingxin
Abstract: Utilization of bionics to develop stimuli responsive polymers that can heal damage with excellent restorability is particularly attractive for a sustainable society. Herein, inspired by chameleons, a hierarchical structural design strategy is proposed and illustrated to fabricate a healable photochromic material based on a self‐healable polymeric matrix and a finely dispersed photochromic spirooxazine. The self‐healable polymeric matrix is fabricated via the integration of multiple hydrogen bonds (H bonds) and covalent cross‐links into a biomass‐derived elastomer. The dynamic nature and soft characteristics enable the as‐prepared elastomer superior extensibility as well as self‐healing ability, while the covalent cross‐links can assist the reassociation of ruptured H bonds. The representative elastomer exhibits an extensibility of 2600% and toughness of 42.76 MJ m −3 . Furthermore, it shows good self‐healing ability with complete recovery of scratch as well as restoration against 1900% of elongation and 24.1 MJ m −3 of toughness after healing at 60 °C for 24 h. This combination of moderate toughness, good self‐healing ability, and smart photochromic property in biomass‐derived materials should largely improve their applicability, reliability, and sustainability in various materials and devices. Abstract : Inspired by chameleons, photochromic materials with appealing photochromism and self‐healing ability is successfully fabricated by integrating biomass‐derived supramolecular elastomer with spirooxazine.